Instant cosmology - Nissan Itzhaki; Uri Peleg (Journal of High Energy Physics)
Abstract Instant Folded Strings (IFSs) are unconventional light strings that emerge when the string coupling increases with time. A particularly intriguing property of IFSs, especially relevant to cosmology, is that they violate the Null Energy Condition (NEC). In this paper, we begin to explore their cosmological effects. We find that NEC violation by IFSs is significantly suppressed in an expanding universe, leading to a universe that resembles our own, comprising matter, radiation, and dark energy. Upon closer examination, these components exhibit subtle, nonstandard traits that could be experimentally tested in the future. Notably, the origin of dark energy stems not only from the potential, as is usually the case, but also from the derivative of the potential with respect to the dilaton. This paves the way for a new approach to realizing inflation within string theory, addressing the Dine-Seiberg problem associated with dilaton stabilization, and perhaps even hinting at a novel mechanism to tackle the cosmological constant problem. Conversely, in a contracting universe, the effects of IFSs are amplified, making bouncing cosmologies a natural and prevalent outcome.